Shift workers are at increased risk of severe COVID-19 compared with day workers: Results from the international COVID sleep study (ICOSS) of 7141 workers. (1st February 2023) - Bjorvatn, Bjørn; Merikanto, Ilona; Reis, Catia; Korman, Maria; Bjelajac, Adrijana Koscec; Holzinger, Brigitte; De Gennaro, Luigi; Wing, Yun Kwok; Morin, Charles M.; Espie, Colin A.; Benedict, Christian; Landtblom, Anne-Marie; et al.
ABSTRACT: The present study had two main aims. First, to investigate whether shift/night workers had a higher prevalence and severity of COVID-19 compared with day workers. Second, to investigate whether people regularly working in face-to-face settings during the pandemic exhibited a higher prevalence and severity of COVID-19 compared with those having no need to be in close contact with others at work. Data consisted of 7141 workers from 15 countries and four continents who participated in the International COVID Sleep Study-II (ICOSS-II) between May and December 2021. The associations between work status and a positive COVID-19 test and several indications of disease severity were tested with chi-square tests and logistic regressions adjusted for relevant confounders. In addition, statistical analyses were conducted for the associations between face-to-face work and COVID-19 status. Results showed that shift/night work was not associated with an increased risk of COVID-19 compared to day work. Still, shift/night workers reported higher odds for moderate to life-threatening COVID-19 (adjusted odds ratio (aOR) = 2.71, 95%-confidence interval = 1.23–5.95) and need for hospital care (aOR = 5.66, 1.89–16.95). Face-to-face work was associated with an increased risk of COVID-19 (aOR = 1.55, 1.12–2.14) but not with higher disease severity. In conclusion, shift/night work was not associated with an increased risk of COVID-19, but when infected, shift/night workers reported more severe disease. Impaired sleep and circadian disruption commonly seen among shift/night workers may be mediating factors. Working face-to-face increased the risk of COVID-19, likely due to increased exposure to the virus. However, face-to-face work was not associated with increased disease severity.